Cowgirl up! : a history of rodeoing women - Thomas, Heidi M. (Guilford, Connecticut : Twodot, 2014)
Recounts how women became involved in rodeos from the late nineteenth century to the first half of the twentieth, describing how some women who learned to rope and ride became attracted to the freedom and the excitement of rodeo competition.
Includes bibliographical references (pages 189-191) and index.
Keywords: Cowgirls -- West (U.S.) -- History; Rodeos -- West (U.S.) -- History; Women rodeo performers -- West (U.S.) -- History; Women in rodeos; BIOGRAPHY & AUTOBIOGRAPHY -- Women; Cowgirls; Rodeos; Women in rodeos; Women rodeo performers; United States, West; History